SYSTEM DESIGN FOR EARLY DETECTION OF DIABETES MELLITUS USING IOT-BASED NON-INVASIVE SENSORS - Widya, Afni Rara; Handayani, Ade Silvia; Rakhman, Abdul (STKIP PGRI Tulungagung, 2025)
This research aims to design a diabetes mellitus early detection tool using IoT-based non-invasive sensors. This tool uses blood pressure sensors and color sensors to detect glucose levels in urine. The data obtained from these sensors is sent to the Arduino Uno microcontroller, displayed on the LCD screen, and saved to the Firebase platform for further monitoring and analysis. The test results show that this tool is able to measure and display blood pressure data and urine glucose levels accurately and in real time so that it can be used as a practical and efficient diabetes mellitus diagnostic tool. This research makes a very important contribution to the development of IoT-based health technology, especially in facilitating early detection of diabetes non-invasively. This research aims to design a diabetes mellitus early detection tool using IoT-based non-invasive sensors.